2008
DOI: 10.1108/09513540810875644
|View full text |Cite
|
Sign up to set email alerts
|

Personal development planning under the scope of self‐brand orientation

Abstract: PurposeThe purpose of this paper is to contribute to the empirical body of knowledge regarding the role of universities today. In addition, it aims to investigate the topic of personal development planning (PDP) programs, under a different perspective borrowed from marketing theory, namely, the “self‐brand orientation” approach.Design/methodology/approachThe study focused on investigating the core research topics and parameters perceived to be important to students. The theoretical perspectives of PDPs and bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…• Article 21 indicated that the sample of the study was limited to business students from a single business school (McCorkle et al 2006). • Article 27 indicated that the research finding did not present a picture of the entire student population (Rigopoulou & Kehagias 2008). • In Article 29, a low response rate influenced the results negatively (Schults & Sheffer 2012).…”
Section: Limitationsmentioning
confidence: 99%
“…• Article 21 indicated that the sample of the study was limited to business students from a single business school (McCorkle et al 2006). • Article 27 indicated that the research finding did not present a picture of the entire student population (Rigopoulou & Kehagias 2008). • In Article 29, a low response rate influenced the results negatively (Schults & Sheffer 2012).…”
Section: Limitationsmentioning
confidence: 99%
“…The essence of this habit is to find out, first, what you want and, then, start planning backward, all the way to your current situation. Rigopoulou and Kehagias (2008) state that there is a gap between demand and supply in investigating student needs and university programs. They go on to say that personal development programs and, generally, college offerings focused on the self are considered valuable by most students because they are interested and willing to enroll in them.…”
Section: Discussionmentioning
confidence: 99%
“…Employees’ innovation behavior is affected by not only the external leadership environment but also individual factors. Research at home and abroad showed that personal development support has a significant influence on employees’ innovation behavior ( Rigopoulou and Kehagias, 2008 ), but previous research failed to provide a clear answer on how this influence works. In addition, participative decision making was confirmed by a large number of studies to have an influence on the innovation behavior of employees within an enterprise ( Sarafidou and Chatziioannidis, 2013 ; Huang et al, 2015 ; Wilson, 2016 ; Salomé and Andrea, 2017 ), and delegation of authority typically emerges in the process of corporate management ( Li L. et al, 2020 ; Liu X. et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%